(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Midwifery educational institutions have an important role in the scoring power of professional and qualified midwives. To be able to produce a professional midwife as expected, then it takes a model of effective and innovative learning. Objective: To know the effectiveess of reflective learning on Student Academy Midwifery Yogyakarta. Method: This type of research survey with descriptive study. The research at Academy of Midwifery in Yogyakarta. Sample student research level I, II, and III. Sampling using a minimum sample size. Variable independent variable research, namely is the reflective learning. The dependent variable is the attitude of professional midwifery students. Result: The result showed statistical significance (P <0.05) between the independent variable (reflective learning) with the dependent variable (professional attitude) with a prevalence ratio 2.13 95% CI (1.62 to 2.78). Conclusion: Students who did reflective learning finely will have a chance to do a good professional attitude. Keywords: Reflective learning, professional attitude, midwifery student